The intersection of science and television representation of gay sexuality in American culture: A shift from the anti-discrimination narrative to the Born This Way narrative. (1st March 2020) - Ngo, Quang
An investigation into the parallelism between media portrayals of gay individuals and the findings produced by the science community can offer possibilities to comprehend the intersection of science and popular culture on the topic of homosexuality. Recognizing this relationship renders it possible to address the historical evolution of media representations of homosexuality alongside the development of scientific knowledge on the same issue. That is, mainstream media can be perceived as a space in which perceptions of what gayness is and means has been negotiated. In this article, I set out to trace how media representations of gay sexuality have shifted from survival to legitimate presence by looking at the adoption of the Born This Way narrative as a new approach to understand homosexuality. To this end, the Born This Way narrative allows for thoughtful and productive representations of gay characters on mainstream television programmes, which the anti-discrimination narrative lacks.